Sedentary behavior and functional disability in older adults with low economic status: Monidi Study - Tatiana Lima Brandão; Kelly Nascimento Lago; Saulo Vasconcelos Rocha (Universidade Federal de Santa Catarina, 2019)
Excess time spent in sedentary activities may intensify functional losses among the elderly; however, information on the amount of time in sedentary activities related to these losses is still incipient. The aim of this study was to determine the predictive power of sedentary behavior (SB) and to establish cutoff points for functional disability (FD) discriminators in the elderly. A cross-sectional study was carried out with sample of 310 older adults with mean age of 71.62 ± 8.15 years, randomly selected and residents in the municipality of Ibicuí-BA. Sedentary behavior was assessed by measuring the time spent sitting on a usual week day and FD weekend and FD by the Lawton scale. Receiver Operating Characteristic (ROC) curves were constructed and SB discriminant criterion for FD was determined. The areas under the curve showed that SB has reasonable potential to discriminate FD. The times spent in SB that best discriminated FD were > 330 minutes / day and > 270 minutes / day for men and women respectively. Time spent in SB is an important health indicator and can be used in the screening of FD in the elderly.